Survival and causes of failed amalgam restorations - Shama Asghar; Farheen Fatima (Journal of Bahria University Medical and Dental College)
Objective: To determine the reasons for failure of amalgam restorations and evaluate the association between the reasons for failure of restorations with gender, classes of cavities, and teeth involved. Materials and Methods: This cross-sectional study was carried out in the Operative Department of Dental Section of Bahria University Medical and Dental College Karachi, from June 2013 to February 2014.Patients were selected randomly who had presented with complaint in amalgam restoration. Specially designed proformas were used to get the information such as the name of the patient, age, gender, teeth in need for replacement of restorations, age of the restorations and the reasons for failed restorations. The criteria for failed amalgam restorations were secondary caries, improper proximal contact, fractured restoration and gingival irritation due to overhang. Chi-square test was applied to get the significance of the result. Results: A total of 141 patients with failed amalgam restorations were examined. The mean age was 40 (±16.18). In all 95 molar and 46 premolar teeth were observed. Secondary caries was leading reason for failure of amalgam restorations (44.68%), followed by gingival irritation due to overhang (17.02%), and margin fracture (12.05%). The mean of longevity of amalgam restoration was 5 years. Chi-square test showed significant association between causes of failure and duration of restorations, different classes of cavities (p-value <0.000) and insignificant relationship with gender (P-value < 0.67). Conclusion: Secondary caries was the most common cause of failure of amalgam restoration in Class II cavities.